Providing Lego And Puzzle Method To Improve Children's Fine Motor Development - Damanik, Syahroni; Harahap, Hasanah Pratiwi; Zuiatna, Dian (Jurnal Kebidanan Khatulistiwa, 2024)
Background: According to UNICEF 2018, there are 10 million disorders in pre-school aged children, as many as 38%, and according to WHO, pre-school aged children suffer from mild brain function disorders as much as 5-25%, while in Indonesia children who experience fine motor development of this disorder are as many as 16% of all children in Indonesia. Objective: To determine the use of Lego and puzzle methods to increase the fine motor development of preschool children. Method: This research used Quasy Experiment Design (using One Group Pretest-Postest Design. The population and sample in this research were all postpartum mothers totaling 30 people. This research used a proportional sampling technique with univariate and bivariate analysis with the T test. The research was obtained from data analysis using the dependent t test. Results: The table shows that the P-Value (0.000), (0.001) < 0.05 means Ho is rejected and Ha is accepted, which means that there is an influence of giving the Lego Method and the Puzzle Method on Increasing Children's Fine Motor Development PAUD at Nurul Iman Children's Park, and obtained a habwa value of 0.698 > 0.05. Conclusion: There is an influence of giving Lego and the Puzzle Method on Increasing the Fine Motor Development of PAUD Children and there is no difference between giving the Lego method and the puzzle method on increasing fine motor development. from preschoolers.gentle towards preschoolers.